Inverting the pyramid : a history of football tactics / Jonathan Wilson. - Wilson, Jonathan. (Orion, 2008)
Soccer fans love to argue about the tactics a manager puts into play, and this fascinating study traces the world history of tactics, from modern pioneers right back to the beginning, where chaos reigned. Along the way, author Jonathan Wilson, an erudite and detailed writer who never loses a sense of the grand narrative sweep, takes a look at the lives of the great players and thinkers who shaped the game, and discovers why the English in particular have proved themselves so "unwilling to grapple with the abstract." This is a modern classic of soccer writing that followers of the game will dip into again and again.